Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Does anyone have idea for solution (for all non-zero numbers)?

$$\ x ≠ 0,y ≠ 0$$

$$\ f: R \setminus \{0\} → R$$

$$\ x \cdot f(xy)+f(-y)=x \cdot f(x)$$


share|cite|improve this question
Is that equation supposed to be true for all $x$ and $y$? For some pair $x$ and $y$? For some function $y$ of $x$? For some function $x$ of $y$? – Chris Eagle Dec 2 '12 at 15:56
for all non-zero numbers – miloshavlicek Dec 2 '12 at 15:58
Right, now put that in the question. Important facts should not lurk in the comments. – Chris Eagle Dec 2 '12 at 15:59
The nil function works! Do I get a candy for finding a solution? – gniourf_gniourf Dec 2 '12 at 16:41
If you will say me how to solve it, I will be incredibly thankful :-) – miloshavlicek Dec 2 '12 at 16:48
up vote 3 down vote accepted

I can solve this completely given the additional assumption that $f$ is continuously differentiable on its domain. I suspect that it's possible to relax this to merely "continuous", but you'll probably need some sort of niceness assumption to get anywhere.

If we set $x=1$, the functional equation becomes $$ f(y)+f(-y)=f(1) \, . $$ So the equation is equivalent to $$ x \, f(xy)-f(y)+f(1)=x \, f(x) \, , $$ which I will suggestively rewrite as $$ x[f(xy)-f(x)]=f(y)-f(1) \, . $$

Now, restrict to the case where $y$ is positive and set $y=1+\epsilon$. Since $f$ is differentiable, we can apply the mean value theorem to find $c_\epsilon \in [x, xy]$, $d_\epsilon \in [1, y]$ such that $$ f(xy)-f(x)=x \epsilon \, f'(c_\epsilon)\\ f(y)-f(1)= \epsilon f'(d_\epsilon) $$ (where we take the convention that interval endpoints are commutative: that is, if $a>b$, $[a,b]=[b,a]$).

So our equation becomes $$ x^2\epsilon f'(c_\epsilon)=\epsilon f'(d_\epsilon) \, . $$ But $f'$ is continuous by assumption, and we have $\lim_{\epsilon \to 0} c_\epsilon=x$, $\lim_{\epsilon \to 0} d_\epsilon=1$. So, passing to the limit, $$ x^2 f'(x)=f'(1) \, ; $$ that is, $f'(x)=\frac{C}{x^2}$ for all $x$ and some constant $C$, and so $f(x)=\frac{C}{x}+D$ for all $x$ and some constants $C,D$.

Now, we can plug this $f$ back into the original functional equation to find which values of $C,D$ actually work. After a little bit of algebra, we see that the left-hand side of the equation reduces to $D+Dx$, while the right-hand side reduces to $C+Dx$. So we must have $C=D$.

That is, the continuously differentiable $f$ which satisfy the equation are precisely those of the form $f(x)=C(1+\frac{1}{x})$ for some constant $C$.

share|cite|improve this answer

Partial Solution

$$ x \cdot f(xy)+f(-y)=x \cdot f(x)$$

Multiplying by $y$ we get

$$ xy \cdot f(xy)+yf(-y)=xy \cdot f(x) \,.$$

We define a new function $g(t):= tf(t) $.

Then, the functional equation becomes

$$g(xy)-g(-y)=yg(x) \,.$$



In particular, we get

$$\frac{g(xy)-g(-y)}{xy+y}=\frac{g(x)}{x+1} \,.$$

It is easy to see that $g(-1)=0$. Thus, with the extra assumption that $g(t)$ is differentiable at $-1$, by setting $x \to -1$, we get that $g$ is differentiable at $-y$ and $g'(-y)=g'(-1)$. Let $g'(-1)=C$, then $g(t)= Ct+D$ for some constants $C,D$, and the functional equation Yields $c=d$.

share|cite|improve this answer

I guess there doesn't lies any solution to this one . Replacing all y's by x. We get x∗f(x^2)+f(−x)=x∗f(x)....(1)in this equation if we put x=1,we get f(-1)=0 .So let us consider there lies a function Q(x) such that , f(x)=(x+1)Q(x). Replacing the f(x) in equation (1) we get one more equation, if we consider the lading coefficient of Q(x) be a1, and it be of degree n.....we see that n=0. so there doesn't lie a function as Q(x). we get f(x)=(x+1);which actually does't satisfy equation 1. so we conclude that f(x) is a constant function and is identically equal to zero.

ALTERNATIVELY considering the given functional equation if we differentiate both sides with respect to x we get

share|cite|improve this answer
The first solution works only for polynomials... The second one only for differentiable functions.... – N. S. Dec 2 '12 at 17:17
I am sure that there is at least one possible solution. – miloshavlicek Dec 2 '12 at 17:20

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.